PENGARUH ETIKA GURU TERHADAP AKHLAK SISWA: Studi di Madrasah Tsanawiyah Rihlatul Ummah Cilegon - Nurhayati, Is; Rahmawati, Novi Tria (THORIQOTUNA: Jurnal Pendidikan Islam, 2018)
Ethics restrictions of human behavior. All forms of his actionscling to the norm. Ethics is very important for everyone, because ifwithout ethics then someone will arbitrary without thinking ofconsequences that will be caused after the event. Teacher ethics is veryinstrumental in the formation of student behavior in school and inenvironment. This research aiming to know teacher ethics at MTsRihlatul Ummah. To know moral students at MTs Rihlatul Ummah. Toknow the influence of teacher ethics on student morals at MTs RihlatulUmmah. Data collection technique used through observation andquestionnaire. Data collected analyzed using statistical approachproduct moment correlation. Result of research is there is a positiveinfluence and significant between teacher ethics with student morals atMTs Rihlatul Ummah with the level of the correlation coeffesient in theamount of 0,78 (strong). This matter proven with degree of significancethat is at ttabel the level significance 5% in the amount of 1,67 and thitung10,64 which means thitung > ttabel. As for contribution variable X withvariable Y in the amount of 61%, the meaning 61% student morals atMTs Rihlatul Ummah associated with teacher ethics.